Film Industry as Part of Global Creative Industry: Learning from Indonesia - Ulum, Mohammad Bahrul; Jannah, Faizzatul; Nadhiyah, Fikriyatun (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2021)
This paper describes the post-reform Indonesian film industry as one of the creative industry sub-sector. The creative industry has contributed to developing a city and a country to increase the market and the global economy. Creative industries have great potential to boost the economy and the quality of life of the Indonesian people. The international film industry can obtain revenue up to $10,162,657,657 (approximately IDR 980 trillion), with ticket sales reaching 1,276,715,780 pieces and the number of moviegoers went more than a 700million people. Meanwhile, in Indonesia, according to research by Oxford Economics, considering the direct and indirect transactions caused, the total economic contribution of the film and television industry to GDP in 2010 reached USD 2.98billion or 0.43 percent of all national GDP. This study aims to analyze three sub-sectors of the film industry, namely production, distribution, and exhibition, as well as to describe how the conditions in the national film industry in the post-reform era since the film industry was lined up as one of the sub-sectors of the creative industry.